Unmasking the Grey Swan : Investor Biases in Times of Turbulence - K. A., Safeeda; R., Ganesh (Indian Journal of Finance, 2024)
Objective : This study examined the disposition effect in the Indian stock market during the steady â€œwhite swanâ€ and uncertain â€œgrey swanâ€ phases induced by COVID-19 to analyze the variations in investor biases influenced by market conditions. This study also tested the capacity of two techniques to elucidate the disposition effect during these periods. Methodology : The disposition effect among the constituent stocks of the Nifty50 index was examined during the white swan (Jan 2019â€“Dec 2019) and grey swan (Jan 2020â€“Dec 2021) phases using the security vector autoregression (SVAR) model and a regression model. Findings : The study emphasized the impact of uncertainty on the prejudices of investors in the Indian stock market. The uncertainty and dread of the market during the grey swan phase affected equities more than it did during the white swan period. The regression model proved ineffectual in identifying the disposition effect, but SVAR indicated the existence of bias. Practical Implications : Market participants and regulators could create robust investment strategies and manage uncertainty by having a thorough understanding of the disposition impact and its variations. It also provided academics with important insights into the efficacy of various methods for tracking the disposition effects. Originality : The disposition effect was compared in the white and grey swan phases in this study. Using different methodologies yielded unique insights into the effectiveness of different ways of tracking the disposition impact.